Visual Methodology in Classroom Inquiry: Enhancing Complementary Qualitative Research Designs - Kingsley, Joanne (Alberta Journal of Educational Research, 2010)
This article presents the argument that combining visual methods with other qualitative research methods enhances the inherent strengths of each methodology and allows new understandings to emerge. These would otherwise remain hidden if only one method were used in isolation. In a qualitative inquiry of an elementary teacher’s constructivist literacy practices, categorizing and contextualizing strategies using grounded theory and narrative analysis were juxtaposed with visual analysis. The interactive, interpretive process of moving back and forth between visual and textual data demonstrated the power of visual images to explicate the complexities of classroom practice.